Ultrasound transducer disinfection in emergency medicine practice. Issue 1 (December 2016) - Hoyer, Riley; Adhikari, Srikar; Amini, Richard
Abstract Background External ultrasound transducer disinfection is common practice in medicine. Unfortunately, clinically significant organisms, such as methicillin-resistantStaphylococcus aureus (MRSA), Pseudomonas aeruginosa, andKlebsiella pneumonia spread throughout healthcare facilities via direct contact despite disinfection protocols. Ultrasound transducers and coupling gel provide potential vectors for pathogen transmission, especially in immunocompromised and high-risk patient populations. Our objective was to conduct a survey to investigate the variety of cleaning solutions or sanitary wipes used and evaluate current standard practice for transducer disinfection across emergency medicine training programs in the United States. Findings Eighty-three academic emergency medicine programs participated in this study. Eighty-seven percent (95 % CI 80–94 %) of responding programs do not have a mandated protocol or standard contact time for transducer disinfection. Ninety percent (95 % CI 84–96 %) of institutions use disinfectant solution or disinfectant wipes, as the standard of practice, to cleanse ultrasound transducers after every use. Conclusions Currently, there is a great deal of variability with regard to non-endocavitary transducer disinfection protocols that seems to stem from the vast number of disinfectant products and ultrasound manufacturer disparate recommendations. In order to mitigate risk to patients and reduce health care costs linked to nosocomial infections; healthcare providers, ultrasound companies, and disinfectant manufacturers must develop a universal use disinfectant and a standard protocol for ultrasound device disinfection for noncritical device disinfection in the emergency department.